Surgical tactics for management of pulmonary nodules in a TB hospital - S. A. Belov; A. A. Grigoryuk (Туберкулез и болезни лёгких)
The objective of the study: to determine the efficacy of surgery for diagnosis of pulmonary nodules in patients of a TB hospital.Subjects and methods. 220 surgeries performed due to pulmonary nodules in 2015-2017 were analyzed, all surgeries were carried out in Primorsky Regional Clinical TB Dispensary of the city of Vladivostok.Results. To determine the etiology of pulmonary nodules, resection was performed in 89 (40.5%) patients, video-assisted thoracoscopic resection in 68 (30.9%), atypical resection in 43 (19.5%), and 20 (9.1 %) patients underwent extended resection of the lung.A histological test of surgical specimens confirmed pulmonary tuberculosis in 179/220 (81.4%; 95% CI 75.7-86.0%) patients. Microbiological tests detected multiple drug resistance in 39/179 (21.8%) cases; this fact was taken into account when prescribing subsequent anti-tuberculosis chemotherapy. Peripheral lung cancer was detected in 19/220 (8.6%; 95% CI 5.6-13.1%) patients, metastatic lesions – in 2/220 (0.9%), benign tumor (chondroma) – in 17/220 (7.7%), and lung cyst in 3/220 (1.4%). Thus, non-tuberculous etiology of pulmonary nodules was present in 41/220 (18.6%; 95% CI (14.1-24.3%) patients referred to TB hospital for diagnostic purposes.